"Slim down" with a ticket to ride: A systematic literature review. (March 2022) - Janatabadi, Fatemeh; Ermagun, Alireza
Abstract: Introduction: The results of examining the nexus of weight loss and physical activity associated with transit use are mixed. Proponents claim that public transit use is positively associated with weight loss, as it indirectly contributes to active commuting for access and egress. Opponents, however, argue that proof of the effects of transit use on weight loss is expected to be indecisive and practically insignificant. Methods: This study evaluates the sources of contention between proponents and opponents by systematically reviewing 54 research articles through a rigorous investigation of the source, type, and size of the data alongside baseline Body Mass Index (BMI), transit-use, and access to transit. The review process consists of (1) establishing the criteria of the review, (2) determining the proper keywords, (3) collecting relevant articles from online databases, (4) assessing the eligibility of the articles, (5) eliminating irrelevant results and determining the primary database, (6) conducting a descriptive analysis, (7) synthesizing the data and report the findings, and (8) presenting the conclusions and offering suggestions for further studies. Results: Three broad patterns can be discerned. First, neither positive nor negative statistically significant association asserted in the existing literature is practically significant. This means, in practice, transit use has no meaningful contribution to weight loss. Second, much of the research employs the cross-sectional design corroborating a correlation rather than causation between transit use and weight loss. Third, neither positive nor negative causation between transit use and weight loss is firmly concluded by research with a longitudinal design. The analysis suggests contradictory outcomes increase as studies employ secondary data, cross-sectional design, access to transit, and self-reported measures. Conclusions: Findings may be a valuable reference point for researchers and practitioners to reevaluate their interpretation derived from the scientific literature on the association between transit use or access to transit and weight loss. This review assists in distinguishing facts from theories and offers a perspective to diminish the risk of indistinct future outcomes. Highlights: In practice, transit use has no meaningful contribution to weight loss. Positive or negative causation between transit use and weight loss is not firmly concluded. Contradictory results increase as studies employ secondary data and cross-sectional design. High baseline BMI can lead to imprecise results and false-negative findings. Racial differences in BMI and weight change can impact the general conclusion.